2011
DOI: 10.4103/1658-354x.84097
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to compare pregabalin with gabapentin for postoperative pain in abdominal hysterectomy

Abstract: Background:Pregabalin is a potent ligand for alpha-2-delta subunit of voltage-gated calcium channels in the central nervous system, which exhibits potent anticonvulsant, analgesic and anxiolytic activity. The pharmacological activity of pregabalin is similar to that of gabapentin and shows possible advantages. Although it shows analgesic efficacy against neuropathic pain, very limited evidence supports its postoperative analgesic efficacy. We investigated its analgesic efficacy in patients experiencing acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 29 publications
12
51
1
1
Order By: Relevance
“…In contrast to our study, the previous study of Ghai et al [49] comparing between three groups of patients undergoing abdominal hysterectomy where the Patients received either 300 mg pregabalin, or gabapentin capsules 900 mg or placebo capsules given at 1 -2 hours before surgery, patients of gabapentin and pregabalin groups had significantly higher sedation scores compared to placebo group (P < 0.001).…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast to our study, the previous study of Ghai et al [49] comparing between three groups of patients undergoing abdominal hysterectomy where the Patients received either 300 mg pregabalin, or gabapentin capsules 900 mg or placebo capsules given at 1 -2 hours before surgery, patients of gabapentin and pregabalin groups had significantly higher sedation scores compared to placebo group (P < 0.001).…”
Section: Discussioncontrasting
confidence: 53%
“…Similar results have been observed by Ghai A study. 21 Oral pregabalin and Gabapentin are useful adjuvants for the management of post operative pain by providing analgesia through a different mechanism than opioids making addition of multimodal therapy if not as sole analgesic and higher patient satisfaction. The apparent strength of this study is 300 mg of pregabalin is selected compared to lower doses as low dosage does not produce an effective pain relief as observed by Peach et al…”
Section: 6mentioning
confidence: 99%
“…Pregabalin has analgesic, anticonvulsant, and anxiolytic effects [5,6]. Several studies have demonstrated the efficacy of oral pregabalin on post-operative analgesia and reduction of parenteral analgesics [7][8][9]. Oral pregabalin attenuates pressor response to laryngoscopy and endotracheal intubation [10,11].…”
Section: Introductionmentioning
confidence: 99%